Association of zinc deficiency and risk of new-onset dementia: a retrospective cohort study - Huang, Sheng-Han; Weng, Hsiu-Lan; Hung, Kuo-Chuan; Ho, Chun-Ning; Tsai, Wen-Wen; Lai, Yi-Chen; Wu, Jheng-Yan; Chen, I-Wen (Frontiers in Nutrition, 2025)
BackgroundZinc deficiency may contribute to cognitive decline through neuroinflammation and synaptic dysfunction; however, epidemiological evidence linking zinc deficiency to incident dementia remains limited. We investigated whether zinc deficiency is associated with an increased risk of new-onset dementia in a large healthcare population.MethodsWe conducted a retrospective cohort study using the TriNetX Research Network and analyzed adults aged ≥50 years who underwent serum zinc testing between January 2010 and December 2023. Patients were stratified by zinc levels: deficiency (<70 μg/ml) vs. normal (70–120 μg/ml). After excluding those with pre-existing cognitive impairment or conditions affecting zinc metabolism, we performed 1:1 propensity score matching based on demographics, comorbidities, medications, and laboratory parameters. The primary outcome was new-onset dementia within 3 years. Cognitive impairment was assessed as an additional outcome, whereas pneumonia was included as a positive control outcome to validate the study's analytic approach.ResultsAfter propensity score matching, 34,249 patients were included in each group. Zinc deficiency was associated with a 34% increased dementia risk (adjusted HR 1.34, 95% CI 1.17–1.53, p < 0.001) and 72% increased pneumonia risk (adjusted HR 1.72, 95% CI 1.63–1.81, p < 0.001). Cognitive impairment showed no significant association in the primary analysis (adjusted HR 1.08, 95% CI 0.92–1.28, p = 0.339) but became significant when the analysis was restricted to the pre-pandemic period (2010–2019, adjusted HR 1.38, 95% CI 1.11–1.72, p = 0.004). A clear dose-response relationship emerged when comparing both mild-to-moderate deficiency (50–70 μg/ml, adjusted HR 1.26, 95% CI 1.10–1.46) and severe deficiency (<50 μg/ml, adjusted HR 1.71, 95% CI 1.36–2.16) against normal zinc levels.ConclusionZinc deficiency represents an independent, modifiable risk factor for new-onset dementia with a clear dose-response relationship. These findings support the consideration of zinc status assessment and optimization in dementia prevention strategies. Future randomized controlled trials are warranted to establish causality and determine optimal intervention protocols.